The marketing strategy and implementation of strategic business units: How to choose a methodology of segmentation strategic marketing? - Magalhães, Miguel (2019)
Since 1923, the application of the methodology of Strategic Business Units (SBUs) has been gaining more followers due to an increasingly unpredictable economic environment and the need for ever growing adaptive products and services directed at the wishes of the elected target (Personalization). Therefore, it becomes essential to perform a prior study to assess which is a better Methodology to perform the strategic marketing segmentation, and for that, we should choose which Criteria to elect in order to better identify: (1) What is the current business of the organization? (2) What business should be deinvested due to the fact that they have ceased to be profitable or if there is a foreseeable decline in that target? (3) And lastly, if it is or not possible to identify new investment opportunities where new business can be developed? By getting answers to these questions, it will be possible to identify current and potential SBUs, and set the most suited business model that will allow adjusting the proposition value to each SBUs. Having said that, we will verify that SBUs Methodology is actually facilitating the management and strategic marketing planning process due to the simple fact that it allows organizations to answer three questions which apparently are very difficult to answer: (1) Should strategic marketing Segmentation be carried out in the Formulation or in the Implementation? And; (2) What are the types of Criteria of Strategic Marketing Segmentation that should be selected to set the SBUs? (3) What is the Model Strategic marketing Segmentation that should be adopted to define the SBUs and its Business model? In short, this research work, even after all these years, we will conclude that this Methodology Continues to prove itself as valid and adequate, be it to delimit an organization in SBUs, or in function of this, to define the business model for each current or potential SBUs, thus contributing as facilitator to the design of the business model that allows the enhancement of the Entrepreneurial Entrepreneurship of each SBUs.